1995
DOI: 10.1007/bf00011363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of legume-based cropping systems on nitrogen mineralization potential of Vertisol

Abstract: A b s t r a c tThe quantity and patterns of net mineralization of soil nitrogen (N) were studied in Vertisols under different cropping systems in the semi-arid tropical areas. Eight cropping systems were selected; three contained pigeonpea (PP), one contained PP and cowpea (COP), and two contained chickpea (CP) as legume component crops, one included sequence cropping with nonlegumes during the rainy and postrainy seasons, and one system was kept fallow (F) during the rainy season and sown to sorghum (S) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…This leads to increased crop yields and consequently the amount of residues available to be returned to the soil (Wani et al 1994a;Paustian et al 1997b). Legumes improve soil fertility because of their nitrogen (N)-®xing ability, thus sparing indigenous soil N (Giller & Wilson 1991;Wani et al 1995a). Legumes are grown as intercrops or in rotation with cereals in the SAT and have been important components of sustainable farming systems since ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to increased crop yields and consequently the amount of residues available to be returned to the soil (Wani et al 1994a;Paustian et al 1997b). Legumes improve soil fertility because of their nitrogen (N)-®xing ability, thus sparing indigenous soil N (Giller & Wilson 1991;Wani et al 1995a). Legumes are grown as intercrops or in rotation with cereals in the SAT and have been important components of sustainable farming systems since ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, beneficial microorganisms in bio-fertilizers accelerate and improve plant growth along with protecting plants from pests and diseases which also enhances growth and increases yield (Abou El-yazeid et al, 2007). Moreover, soil microorganisms have a great role in sustainable development of agriculture and this has been reviewed by Lee and Pankhurst (1992) and Wani et al (1995).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in SOC sequestration was evident by a gain of about 7.3 t C ha −1 over a 24-yr period ending in 2000. The results of other longterm experiments with different cropping patterns in Vertisols indicated that legume-based cropping was more sustainable than those with cereals (Wani et al, 1995). The sequestering of atmospheric CO 2 in the soil is a win-win situation since it both improves the soil quality and maintains environmental quality (Wani et al, 2007).…”
Section: Orders Of Tropical Indiamentioning
confidence: 99%